Industry transformations for high service provisioning with lower energy and material demand: A review of models and scenarios - Wiedenhofer, D.; Streeck, J.; Wiese, F.; Verdolini, E.; Mastrucci, A.; Ju, Y.; Boza-Kiss, B.; Min, J.; Norman, J.; Wieland, H.; Bento, N.; Godoy León. M. F.; et al. (Annual Review of Environment and Resources, 2024)
Developing transformative pathways for industry's compliance with international climate targets requires model-based insights into how supply- and demand-side measures affect industry, material cycles, global supply chains, socioeconomic activities, and service provisioning that support societal well-being. We review the recent literature modeling the industrial system in low energy and material demand futures, which mitigates environmental impacts without relying on risky future negative emissions and technological fixes. We identify 77 innovative studies drawing on nine distinct industry modeling traditions. We critically assess system definitions and scopes, biophysical and thermodynamic consistency, granularity and heterogeneity, and operationalization of demand and service provisioning. We find that combined supply- and demand-side measures could reduce current economy-wide material use by 56%, energy use by 40% to 60%, and greenhouse gas emissions by 70% to net zero. We call for strengthened interdisciplinary collaborations between industry modeling traditions and demand-side research to produce more insightful scenarios, and we discuss challenges and recommendations for this emerging field.